An Ecolinguistic look at the works of Moradi Kermani - Hossein Razavian; Tamanna Elahipanah (مطالعات زبانی و بلاغی)
The current research examines the two books Khumrehand Tanour va Dastanhaye digar- written by Houshang Moradi Kermani - from an environmental linguistics (aka. ecolinguistic) approach. In the present study, among Arran Stibbe’s eight environmental stories, five stories of Ideologies, Evaluations, Identities, Erasure, and Salience, have been reviewed and analyzed. Determining the occurrence percentage of stories and analyzing these statistics in the body of research has been done using a descriptive-analytical method. It can be said that there is a downward trend in the level of realization of environmental stories of Salience, Evaluations, Ideologies and Identities. The story of Erasure which has a negative value, shows a small percentage of occurrence in these books. Evaluating stories based on ecosophies suggests that philosophies such as “Valuing life,” “Wellbeing,” and “Respect for the lives of all species” have a high frequency in these texts. Philosophies concerning “Now and future” and “Environmental limits” are also discernible in the research data. Except for two short stories, the stories of these two books show Kermani's positive view of ecosophies. Education plays a very important role in achieving the goals of culturization, value creation and modeling. Among the most valuable resources for promoting environmental cultures are media, books and institutions such as education and pedagogy. Reflecting on children and adolescents’ books can be a way to spread and institutionalize environmental culture.